History and Main Research Currents in Polish Medical Geography - Michalski, Tomasz (Quaestiones Geographicae, 2018)
The main aim of the study is to present the history and the state of research in Polish medical geography. Its origins are the same as in world geography, i.e. it is associated with non-geographers. However, it was developing very slowly till the mid-1980s. Since then a slow increase in the number of publications has been noted (with a noticeable predominance of studies in disease geography over health geography). But still, it must be emphasised that medical geography in Poland is poorly developed.